2017
DOI: 10.1097/mpg.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline as an Additional Treatment for Cholestatic Pruritus in Children

Abstract: Our data suggest that sertraline may constitute a useful drug in the management of refractory cholestatic pruritus in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 19 publications
(22 reference statements)
0
31
0
Order By: Relevance
“…In a two-armed proof-of-concept study with paroxetine and fluvoxamine, patients with CP of dermatological origin reported a significant antipruritic effect (321). Sertraline proved effective in cholestatic pruritus both in adults (322) and children (323), as well as in CKD-associated pruritus (324,325). In a recent double-blind RCT among 50 haemodialysis patients, sertraline was shown to be effective in reducing uremic pruritus (326), while Doxepin also showed positive effects in 7 patients (304).…”
Section: Gabapentin and Pregabalinmentioning
confidence: 99%
“…In a two-armed proof-of-concept study with paroxetine and fluvoxamine, patients with CP of dermatological origin reported a significant antipruritic effect (321). Sertraline proved effective in cholestatic pruritus both in adults (322) and children (323), as well as in CKD-associated pruritus (324,325). In a recent double-blind RCT among 50 haemodialysis patients, sertraline was shown to be effective in reducing uremic pruritus (326), while Doxepin also showed positive effects in 7 patients (304).…”
Section: Gabapentin and Pregabalinmentioning
confidence: 99%
“…3 In addition to cholestyramine, it has been shown that ursodiol, rifampin, naltrexone, and now more recently sertraline can be used to treat pruritus medically in patients with cholestasis. 4 Further research has supported the initial findings by Sharp et al in demonstrating the harmful effects of increased bile acids in cholestasis, as well as the use of cholestyramine as treatment for pruritus in such patients. It remains a topic of discussion with further research needed, given the negative impact that cholestatic pruritus has on patients' lives.…”
mentioning
confidence: 58%
“…[ 13 ] A prospective multicenter study assessed the efficacy and safety of the serotonin reuptake inhibitor sertraline, for the treatment of children with refractory cholestatic pruritus. [ 14 ] Oliveira et al [ 15 ] thought that the genetic defect in PFIC-3 appears to explains the pathogenesis of intrahepatic cholestasis in pregnancy; their understanding may might provide insights into for developing new therapeutics therapies. After analyzing >150 BSEP mutations, Dröge et al [ 16 ] demonstrated that the extent of exon skipping depends on the genomic and cellular contexts, and that regulation of splicing may have therapeutic potential for PFIC-2.…”
Section: Discussionmentioning
confidence: 99%